Organic–inorganic hybrid self-pigmenting effect of anodic aluminium oxide membranes. Issue 44 (7th November 2022) - Zhang, Junxi; Zhang, Wei; Xu, Wei; Xie, Kang; Shan, Qingsong; Fei, Guangtao; Jia, Junhui; Zhu, Xiaoguang; Zhang, Lide; Fan, Zhiyong; Zeng, Haibo
Abstract : The organic–inorganic hybrid self-pigmenting effect of the anodic aluminium oxide membrane exhibits color conversion with the nanochannel size due to the distribution of anion-contaminated species. Abstract : Anodic aluminium oxide (AAO) membranes with hexagonally packed nanochannel arrays have been utilized as a promising template to develop functional nanostructures. The characteristics of the AAO membranes are crucial to their functional applications. Great efforts have been made toward the formation mechanism and fabrication techniques of the AAO membranes, however, the characteristics of the AAO membranes have not yet been sufficiently elucidated. Herein, we present an organic–inorganic hybrid self-pigmenting effect based on the AAO membranes; the color of the AAO membranes demonstrates a conversion from straw yellow to achromaticity by tuning the nanochannel size. Consequently, the nanochannel size can be evaluated macroscopically according to the hybrid self-pigmenting maps. Furthermore, the hybrid self-pigmenting behavior depends on both the composition and structure of the AAO membranes. The organic–inorganic hybrid self-pigmenting process includes a dynamic equilibrium between the formation of the aluminium oxide and the dissolution of the oxide, as well as the migration of the oxalate anions towards the inner layer of the nanochannel under the local electric field. The self-pigmenting based on electrochemical anodization not only presents a new route to realize organic–inorganic hybrid pigmenting but also provides some promising applications in optics, biomedical and industrial fields.